Neuroprotective Effects of Calycosin Against Fenpropathrin-Induced Dopaminergic Neurodegeneration in Drosophila melanogaster (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
The loss of dopaminergic neurones in the substantia nigra pars compacta is a hallmark of Parkinson's disease (PD), a neurodegenerative condition. Environmental pesticide exposure, particularly to pyrethroids such as fenpropathrin (Fen), represents a significant risk factor for PD pathogenesis alongside genetic predispositions. Recently, studies have indicated that exposure to Fen may also increase the likelihood of developing PD. In this study, we validated a Drosophila melanogaster model of neurotoxicity by exposing 2-5-day-old male flied to 5 mg/L fenpropethrin (Fen) for 96 hours. Motor functions were assessed using climbing, jumping, and crawling assays, alongwith survival and pupal development studies. To investigate underlying molecular changes, protein analysis was performed through western blot to evaluatate the expression of the dopaminergic neuron marker tyrosine hydroxylase and the apoptotic marker caspase-3. Subsequently, Calycosin, an isoflavone phytoesterogen obtained from Astragalus membranaceus that has anti-inflammatory, antioxidant, and anti-apoptotic qualities, was evaluated for its neuroprotective effectiveness. Calycosin was tested at concentrations of 50, 100, and 200 µM, with 50 µM identified as the optimal dose on improved survival rates and locomotor performance. Previous studies suggest calycosin’s neuroprotective effects, but its role in fenpropathrin (Fen)-induced neurotoxicity remains unexplored. This study evaluates calycosin’s efficacy against Fen-induced neurodegeration in Drosophila melanogaster. Calycosin significantly improved motor, including a 48% increase in crawling behaviour and a 20% rise in survival rates. It reduced cleaved caspase -3 levels by 16.7%, alleviated developemental delays by 18.9%, and restored tyrosine hydroxylase expression by 44.1%, indicating protection of dopaminergic neurons. These findings demonstrate that calycosin provides significant neuroprotection against Fen-induced neurodegeneration in the Drosophila PD like model, suggesting its potential as a therapeutic intervention for pesticide-related neurodegenerative diseases.